Advances in remote sensing for natural resource monitoring - Pandey, Prem Chandra 1985-; Sharma, Laxmi Kant 1976- (John Wiley & Sons Ltd, 2023)
"Natural resource management using RS technology relies on the process of dealing with or controlling natural resources for better and effective way in order to successfully implement the outcome for societal benefit. These include planning, organizing, staffing, leading and controlling along with proper monitoring. Whereas the term 'monitoring' identifies the set of practices or actions that aims at the observation on the progress or quality of natural resources over a period of time or keep under systematic evaluation using RS technology via either field surveys or airborne or space-borne datasets (NCRI 2020). Therefore, it is an actions that aims at observation of different phenomenon, or a variable which characterizes the different ecosystem, to follow its regular development and/or to highlight the occurrence of critical or alarming conditions (NCRI 2020). Therefore, natural resource monitoring, in particular, is linked to its management which is carried out on the basis of information derived from the earth observation data on their conditions. Natural resource monitoring and management using RS technology ascertain to deliver proper and accurate information to the users about their condition and development. Thus, reliable information on the accurate field inventory along with periodic monitoring of the natural resources using RS technology will help and speed up and enable management and decision makers to implement the policies accordingly. Even information will be used to keep an eye on the optimal utilization of natural resources or any future disasters so as to take timely interventions."